ANALYSIS OF THE CONTENT CAMEO PROJECT YOUTUBE VIDEO IN SUPPORTING ANTI BULLYING CAMPAIGN - Yanis, Fauziah (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2021)
The development of communication technology which is increasingly advancing is shown by the emergence of social media such as Youtube, which is considered a platform that can be used as a means of gaining economic benefits as well as a means of communication in conveying aspirations. The Cameo Project Youtube account in its content entitled "Small Talks That Make You Heartbroken" contains videos that can be related to the association of today's congregants who pay less attention to their communication patterns, so that sometimes consciously or unconsciously hurt the feelings of someone they communicate with. This study focuses on how the contents of the anti-bullying campaign message in the video content delivered by the Cameo Project using the content analysis method. The theory used in this research is social media theory and bullying theory. This study aims to clearly determine the meaning conveyed in the video. The results showed that if the bullying was carried out continuously it would result in conflict within the bully victim, if the victim could not survive against his inner turmoil, there would be bad suggestions for himself which caused the bullying victim to experience interpersonal conflict. In the video that has been analyzed by researchers, it shows that the bullying in the video as a whole is 100% verbal communication. Key words: Content Analysis, Bullying, Youtube Video.